"Ladies and Gentlemen, It's (Not) the Beatles!": Recreating The White Album. Issue 3 (1st September 2020) - Heyman, Matthias
ABSTRACT: Beatles tribute bands offer a make-believe substitute for the "emotional vacuum" left by the band's breakup in 1970. Among the best-known acts are the Bootleg Beatles, who since 1980 have toured the world with elaborate shows consisting of appropriate costumes, hairdos, and Scouse-accented banter. By contrast, the Analogues approach such reenactment quite differently. Downplaying visual mimesis, they strive for complete aural accuracy. This essay compares both tribute bands' approaches to reconstructing The White Album, discussing how they aim to reanimate a fictionalized past in an authentic manner: the Bootleg Beatles to witness an imaginary Beatles performance, the Analogues to hear music that was never meant to be heard live.